(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the interaction between traditional and modern pedagogical approaches in the development of educational culture. It highlights the differences and commonalities between the traditional education system, based on social, cultural, and ethical values, and modern pedagogy, which incorporates technological innovations and advancements. The dialectical processes between the rigid norms of traditional education and the creative, independent thinking promoted by modern education are explored.